Specific neuromuscular responses of high skilled Laser sailors during a multi-joint posture sustained until exhaustion - Maïsetti, O.; Boyas, S.; Guevel, A. (International Journal of Sports Medicine, 2006)
The aim of this study was to examine the myoelectric manifestations of neuromuscular fatigue induced by a sustained bout of hiking with regard to training status, laterality and muscle. Nineteen subjects, separated into three different groups according to their training status in hiking, volunteered to take part in this study. Subjects performed a sustained hiking test until exhaustion at 50 % of the maximal hiking torque on a specially developed hiking ergometer. The electrical activity of two bilateral (left and right sides) muscular chains involved in hiking including the rectus abdominis (RA), rectus femoris (RF), vastus lateralis (VL), and tibialis anterior (TA) muscles was explored using surface electromyography. Results indicated a higher endurance time (Tlim) for the highly trained group in hiking (45 %, p < 0.05). The mean electrical activity of the muscles studied reached a medium level at the end of the sustained hiking period (51 % of maximal values, p < 0.001), regardless of the training status. However, the increase in activation level was delayed in hikers (50 % Tlim) compared to non-hikers (25 % Tlim), especially for rectus abdominis and rectus femoris muscles. Furthermore, activation patterns of synergistic muscles differed among the groups so that electrical activity of knee extensors was higher than that of trunk flexors of hikers at the end of hiking task (e.g., left RA: 32 % vs. left VL: 54 % of maximal values, p < 0.001). Shifts in mean power frequency were more pronounced in rectus abdominis muscles (- 24 %, p < 0.001) than in rectus femoris (- 7 %, p < 0.001) and vastus lateralis (unchanged), regardless of the group. Hikers exhibited a lower and more delayed spectral compression (left side: - 1.3 %, right side: - 9.8 %) compared to non-hikers (left and right sides: - 15.1 %). These findings suggest that hikers prolonged endurance time by adjusting neural distribution of activity among synergists, thereby minimizing the contribution of the most fatigable muscles, such as the trunk flexors.